Development of Mobile App for College Math: MathTech - Moreno, J; Sandoval, M; C. Morales; Castillo, L (International Journal of Computer Sciences and Engineering, 2021)
The development of a mobile Application (Math Tech) is presented, base on the Scrum methodology, which shows an innovative way a set of mathematical formulas and examples of their use for the subjects of mathematics for pre- university courses, linear algebra, differential and integral calculus and operation research of the curricula by Instituto Tecnologico Superior de Comalcalco (ITSC). The App will be a great support in order to improve their abilities in Math. The use of Scrum, given its characteristics, allowed for the programming of the App in a clear, agile and simple way. Additionally, a variety of creative visuals elements have been included that give to the app a higher qualit.